Generic Fluency in Professional Subtitling: : Neology as the Voice of Science Fiction in Audiovisual Translation - Korpi, Suvi (Journal of Audiovisual Translation, 2021)
This article evaluates the translation of neologies in professional subtitling of audiovisual science fiction from the point of view of genre-specific features. Neologies are seen to be the most important linguistic element of science fiction as they produce the science fiction genre-specific cognitive estrangement and hence cognitively estrange the viewer from reality. Evaluating the translation of neologies is thus used as a tool to evaluate the transfer of the source text genre to the target text and to hypothesise whether the target text meets the expectations of the viewers. When the neologies are retained as genre-specific features of science fiction, the target text genre is seen to be generically fluent and the target text meets the viewer’s expectations. Even though the translation solutions which render the genre unfluent (misplace the science fiction cognitive estrangement produced by the source text) are in minority in the study material, the neologies can be seen to normalise towards common language in the translation process. This means that as neologies are considered as one of the producers of the science fiction genre-specific cognitive estrangement, the source text genre becomes less accessible for the target text viewer. Lay summary Science fiction is one of the most popular contemporary film and tv-series genres. The audience has expectations on the content of a science fiction film or tv-series based on their previous experiences with the genre, in other words, the genre-specific features. This article evaluates the translation of neologies in professional subtitling of audiovisual science fiction from the point of view of these genre-specific features. Neologies are seen to be the voice of science fiction as they cognitively estrange the viewer from reality. Evaluating the translation of neologies is used as a tool to evaluate the transfer of the source text (the original tv-series) genre to the target text (the subtitled tv-series) and to hypothesise whether the translation meets the expectations of the viewers. When the dialogue’s neologies are retained in the subtitles, the target text is seen to meet the viewer’s expectations. The study revealed that the neologies can be seen to normalise towards common language in the translation process. This means that as neologies are considered as one of the producers of the science fiction genre-specific cognitive estrangement, the source text genre becomes less accessible for the target text viewer.